Emprego de um MOF de íon Tb3+ fotoluminescente como sensor para metanol em etanol combustível - Fonseca, Ramon Raoni Ferreira da (2018)
The sensing capability of a Tb3+ -metal-organic framework, based on its photoluminescence was used for detection of methanol in ethanol fuel. It was synthesized using terbium and trimesic acid as a metal ion center and ligand, respectively. Powder x-ray diffraction, infrared spectroscopy, thermogravimetric analysis and scanning electron microscopy were employed to characterize the synthesized MOF-76 structural features. According to the results, MOF-76 was successfully obtained with minor synthetic modification and its activated form (named TbTMA) was tested as a sensor for methanol, one of the etanol fuel adulterants. Tb3+ ion luminescence intensity increased as the methanol concentration in ethanol fuel also increased and the water content did not affect this response. Our findings indicated TbTMA as an appropriate sensor for evaluating ethanol fuel adulteration by methanol addition above the allowed limit regulated by Brazilian National Agency of Petroleum, Natural Gas and Biofuel.